2011
DOI: 10.1680/cien.2011.164.5.46
|View full text |Cite
|
Sign up to set email alerts
|

Delivering London 2012: health and safety

Abstract: This paper describes the challenge of managing health and safety during construction of the London 2012 Olympic and Paralympic Games. The workforce on the Olympic Park site in east London peaked at 12 000 and a total of 30 000 people will have worked on the project through its lifetime. Through careful planning, implementation of strategies with a proven track record and clear leadership, the Olympic Delivery Authority managed to achieve an accident frequency rate comparable to the average for all British empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…It has been suggested that in the UK, some contractors were able to record accidents free in their project by means of awareness creation and training as the employees were allowed to participate in the formulation of health and safety policies on their projects (Pollitt, 2006). In the same vein, the Olympic Delivery Authority (ODA) was able to obtain a reduced accident frequency during the construction of the Olympic Park in East London through training of workers on health and safety issues (Shiplee et al, 2011). This amplifies the row worker's training, and awareness creation can contribute to the minimisation of accidents at the construction site.…”
Section: Effective Health and Safety Management At The Construction Sitementioning
confidence: 99%
“…It has been suggested that in the UK, some contractors were able to record accidents free in their project by means of awareness creation and training as the employees were allowed to participate in the formulation of health and safety policies on their projects (Pollitt, 2006). In the same vein, the Olympic Delivery Authority (ODA) was able to obtain a reduced accident frequency during the construction of the Olympic Park in East London through training of workers on health and safety issues (Shiplee et al, 2011). This amplifies the row worker's training, and awareness creation can contribute to the minimisation of accidents at the construction site.…”
Section: Effective Health and Safety Management At The Construction Sitementioning
confidence: 99%
“…Although there has been a proliferation of commentaries by expert practitioners on various aspects of the CDM Regulations in the UK based on reflection on their individual experiences (e.g. Shiplee et al, 2011;Webster, 2013), the literature review uncovered only reports of consultants commissioned by HSE to evaluate the Regulations with a view to appropriate amendments (e.g. Frontline Consultants Ltd, 2012) and empirical studies into the practical implementation of the CDM Regulations (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first of two special issues of Civil Engineering that we produced 2 years ago on delivering the London 2012 Olympic and Paralympic Games, there was a paper on the overall approach to construction health and safety (Shiplee et al, 2011) -no mean feat with a total workforce of 30 000 at the Olympic Park site alone. The third paper in this issue (Webster, 2013) focuses on implementation of the Construction (Design and Management) Regulations 2007 (hMG, 2007) on the project and how this compares with implementation elsewhere.…”
Section: Editorialmentioning
confidence: 99%